2022
DOI: 10.3390/ma15248730
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Organic Rheology-Modifiers (Chemical Admixtures) and Their Effects on the Rheological Properties of Cement-Based Materials

Abstract: Organic rheology modifiers, especially superplasticizers and viscosity-modifying admixtures (VMAs), have become key components for the workability optimization of modern concrete. The development of these admixtures is crucial to the further performance improvement of modern concrete under different casting and service conditions. Many of the former reviews have summarized research advances in respect of these admixtures from chemical and material perspectives, focusing on the effects of structure and the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 194 publications
0
3
0
Order By: Relevance
“…In conjunction with the experimental program, molecular dynamics (MD) simulations will be performed to elucidate AWAcement-water intermolecular interactions at the nanoscale and microscale [10,11]. These simulations can solve Newton's equations of motion for matrix components to determine atomic trajectories and reveal transient binding phenomena [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with the experimental program, molecular dynamics (MD) simulations will be performed to elucidate AWAcement-water intermolecular interactions at the nanoscale and microscale [10,11]. These simulations can solve Newton's equations of motion for matrix components to determine atomic trajectories and reveal transient binding phenomena [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the viscosity reached its maximum at 2% nano-silica content, and larger fly ash content increased the viscosity when used together with the nano-silica additives. In addition, researchers have used various additives such as viscosity modifying agents, superplasticizers, and organic chemical admixtures [21][22][23][24]. In this paper, we are focusing on nano-additives and fly ashes since they have been widely used in cementitious materials and exhibit effectiveness in improving the rheological properties of fresh cement and concrete.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Currently, research on the rheological properties of mortar focuses on the evolution of the microstructure of mortar influenced by organic rheology modifiers, the impact of the chemical structure of mortar on yield stress, the apparent viscosity and thixotropy of mortar, as well as the structural design of organic rheology modifiers such as superplasticizers and viscosity-modifying admixtures. 14 Also, coarse aggregate is excluded in many new generations of cementitious materials, which are the mortar mixtures. Therefore, it is critical to study the rheological behavior of the mortar.…”
Section: Introductionmentioning
confidence: 99%